Performance of Membrane Bioreactor in the Treatment of High Strength Municipal Wastewater - Birima, Ahmed Hussien (2008)
In some parts of Malaysia, wastewater treatment plants (WWTPs) are located in industrial areas. These WWTPs receive wastewater mostly from these industrial activities regularly or occasionally. Therefore, their biochemical oxygen demand (BOD), chemical oxygen demand (COD) and ammonia nitrogen (NH3-N) are very high. Conventional biological treatment processes are incapable of producing desirable effluent quality with the increasingly stringent discharge requirement. In this study, a laboratory-scale membrane bioreactor (MBR) was used for treating high strength municipal wastewater. Prepared synthetic wastewater samples which represent a high strength municipal wastewater as well as the actual high strength municipal wastewater were used in the study. The developed MBR was operated under different conditions using statistical experimental full factorial design with three factors and three levels. The factors were sludge retention time (SRT), feed temperature (Tf) and organic loading rate (OLR) and their respective levels were 25, 30 and 35 days; 20, 30 and 40 oC; and 1.73, 4.03 and 6.82 kg COD/m3 .d . To evaluate the performance of MBR under the different operating conditions, ten trials were carried out using the prepared synthetic wastewater samples. The MBR could cope with the different operating conditions with high accuracy on the experimental results. Permeate COD, BOD, NH3-N and total suspended solids (TSS) varied from 0 to 32, 0.3 to 13.1, 0.004 to 0.856 and 0 to 26 mg/l respectively. The pH in the aeration tank increased significantly compared to that of the feeding tank. In addition, the increasing pH of the aeration tank was well correlated to that in the feeding tank. (R2 = 0.8336 for low OLR trials and 0.9106 for high OLR trials). To investigate the effects of the different operating conditions on membrane fouling, sustainable time (tsust) was used as a measure to compare the different trials. Within the same OLR level, tsust increased as SRT and Tf increased. Sustainable time was found to decrease as the ratio of mixed liquor volatile suspended solids to mixed liquor suspended solids (MLVSS /MLSS) increased with a correlation coefficient (R2) of 0.808. When MBR was used to treat the actual high strength municipal wastewater, the respective average removal efficiencies of COD, BOD and NH3-N were 98.4, 99.7, and 99.9%. These were found to be comparable with those values obtained from the synthetic wastewater treated by MBR . Empirical models were developed to predict the concentrations of permeate COD, BOD and NH3-N. The predicted values were highly correlated with the observed values (R2 of 0.9188, 0.9111 and 0.9899 respectively for the three parameters mentioned). However the models of COD and BOD were found to be more accurate than the NH3-N model. Future work on the optimization of MLSS concentration and aeration rate as well as the improvement on the techniques for reducing the membrane fouling is recommended.